2021
DOI: 10.1080/14992027.2021.1910740
|View full text |Cite
|
Sign up to set email alerts
|

The association between non-communicable disease and hearing aid adoption in older adults with hearing loss

Abstract: Objective. To assess whether specific non-communicable diseases are associated with hearing aid adoption in older adults with hearing loss. Design.A cross-sectional, observational study. Study sample.Data was obtained from one of the largest pharmacy-led health and beauty retailers in the United Kingdom. In total, 17,172 older adults were included. Results. Greater odds of adopting hearing aids were associated with being older (Odds ratio[OR]= 1.03; 95% confidence interval [CI]= 1.02, 1.03), having fewer self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although 16 studies reported no association, eight studies reported that people were more likely to adopt hearing aids if they were older ( Angara et al, 2021 ; Gopinath et al, 2011 ; Maidment & Wege, 2021 ; Saunders et al, 2016 , 2013 ; Sawyer et al, 2020 ; Singh & Launer, 2016 , 2018 ). Conversely, Chang et al (2016) reported that people were more likely to accept a hearing aid if they were younger in an older cohort (65–90 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…Although 16 studies reported no association, eight studies reported that people were more likely to adopt hearing aids if they were older ( Angara et al, 2021 ; Gopinath et al, 2011 ; Maidment & Wege, 2021 ; Saunders et al, 2016 , 2013 ; Sawyer et al, 2020 ; Singh & Launer, 2016 , 2018 ). Conversely, Chang et al (2016) reported that people were more likely to accept a hearing aid if they were younger in an older cohort (65–90 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…Health: The existence of other health problems has a mixed association with hearing aid use. Some studies have found a positive association between comorbidities and hearing aid use [10], whereas other studies have found that lower overall health status [1], and conditions such as hypertension and diabetes [7] can increase the risk of not using hearing aids. We included binary variables for diagnoses of diabetes, osteoarthritis and cardiovascular disorder (heart attack, stroke, angina, deep vein thrombosis or other related condition), which have been found to be related to hearing aid use by Fisher et al [10]).…”
Section: Correlates Of Hearing Aid Usementioning
confidence: 99%
“…Research on hearing help-seeking and hearing aid uptake has tended to neglect ethnicity, meaning that there is little evidence to draw upon to explain the ethnic inequalities in this area. The available body of evidence on correlates of hearing aid use includes a number of reviews [4][5][6], and studies using UK data [1,7,8], yet only two studies among this entire body report results on ethnicity, and only one of these [1] uses UK data. While theories have been proposed concerning the influence of cultural factors on hearing help-seeking and hearing aid uptake (see [9] for a review), there is no direct evidence linking cultural factors to ethnic inequalities in hearing aid use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, the presence of additional health conditions has been shown to be a barrier to hearing loss management (Barnett et al, 2016). For instance, a recent analysis of a large cohort (N = 17,172) based in the United Kingdom (UK) found that cardiovascular ill-health was associated with decreased odds of adopting hearing aids (Maidment & Wege, 2021). Similarly, an Australian based cohort study (N = 1,371) identified that a history of stroke was a significant predictor of reduced hearing aid ownership (Gopinath et al, 2011).…”
Section: Introductionmentioning
confidence: 99%